Analisis Semantik Makna Kias Terjemahan Kitab Suci Dhammapada Bab I Yamaka Vaggo Syair 1-10 - Ayu Candra Setyawan (Jurnal Budi Pekerti Agama Buddha, 2024)
The Dhammapada, a revered Buddhist scripture, is structured in the form of gathas, which are poetic teachings rich in noble values and inspiration for self-development. The beautiful language within the Dhammapada frequently employs lexemes and metaphorical sentences that possess a high degree of vagueness. This vagueness necessitates a literal semantic analysis of meaning so that the text can effectively serve as a guide for ethical and spiritual conduct, as well as a tool for teaching morality, meditation, and wisdom. Semantic studies, which analyze the meaning of lexemes or sentences, are still rarely found within Buddhism. However, semantic studies are crucial for a deep understanding of Buddhist teachings, bridging the gap between literal and philosophical interpretations, and providing a foundation for teaching Dhamma relevant to the modern era. This research utilizes a descriptive method with a literature review approach. The results of the semantic study on the figurative meanings within the Dhammapada indicate that a right view (samma ditthi) regarding unwholesome and wholesome actions can be achieved through mind control, management of the six senses, and eradication of mental defilements (kilesa).